COMPARISON OF DAY AND NIGHT CATCH WITH DRIFT GILLNET GEAR IN THE OF PASAR II NATAL MANDAILING NATAL REGENCY NORTH SUMATERA PROVINCE - Kholidin Yunus Nasution; Bustari Bustari; Ronald Mangasi Hutauruk (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTDriftgillnets are gill nets in which the way of operation is left to be washed away in the water, whether it is washed away on the surface, water column or at the bottom of the water. This study aims to calculate the number of catches of driftgillnet during the day and nightin the District of Natal. The method used in this study is a survey method, where research data are obtained directly to the field by evaluating thedrift gillnet fishing gear operated by fishermen in Natal District.The date analysis used in this study was a t-test (Sudjana, 1982) to find the difference between day and night catches. From the result of the calculation of t-test catches during the day and night there are differences in catches, namely by and db= 32, then obtained thit= -3,77, is outside the receiving area H0 so that the alternative hypothesis H1 is accepted, meaning that there are differences in catch based on the amount of weight (kg) during the day and night. While to find out the differences in catch based on the number of individuals (tails) namely with and db= 38, then obtainedthit= -3,333, is outside the receiving area H0 so that the alternative hypothesis H1 is accepted, meaning that there are differences in catch based on the number of individuals (tails) during the day and night.Keywords: drift gillnet, catch comparisons, catches day and night